2017
DOI: 10.1016/j.jhep.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir disoproxil fumarate (TDF) vs. emtricitabine (FTC)/TDF in lamivudine resistant hepatitis B: A 5-year randomised study

Abstract: The goal of oral antiviral treatment for chronic hepatitis B (CHB) is to achieve and maintain undetectable HBV DNA levels. Treatment options with enhanced potency, and low risk of resistance development for patients infected with lamivudine resistant (LAM-R) HBV are required. Tenofovir disoproxil fumarate (TDF) monotherapy was effective and well tolerated without TDF resistance development in CHB patients with LAM-R, for up to 240weeks. Clinical trial number: NCT00737568.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
48
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 31 publications
(54 reference statements)
9
48
0
Order By: Relevance
“…In phase III clinical trials of TDF, there was no evidence of TDF resistance among 641 NA‐naïve patients who received TDF for up to 8 years, and most cases of virological breakthrough were attributed to nonadherence . Similarly, in another study of 280 patients with lamivudine resistance who received TDF alone or in combination with emtricitabine for up to 240 weeks, TDF resistance was not found . Although long‐term data on risk of resistance with TAF are lacking, no resistance has been reported in clinical trials with 2‐year follow‐up …”
Section: Management Of Chronic Hbv In Special Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In phase III clinical trials of TDF, there was no evidence of TDF resistance among 641 NA‐naïve patients who received TDF for up to 8 years, and most cases of virological breakthrough were attributed to nonadherence . Similarly, in another study of 280 patients with lamivudine resistance who received TDF alone or in combination with emtricitabine for up to 240 weeks, TDF resistance was not found . Although long‐term data on risk of resistance with TAF are lacking, no resistance has been reported in clinical trials with 2‐year follow‐up …”
Section: Management Of Chronic Hbv In Special Populationsmentioning
confidence: 99%
“…In vitro studies showed that susceptibility of adefovir‐resistant HBV, with a single N236T or A181V/T mutation, to TDF is minimally changed compared with wild‐type HBV, but susceptibility is lower when both mutations are present. Clinically, most studies have found that TDF is effective in suppressing adefovir‐resistant HBV without any benefit from adding emtricitabine …”
Section: Management Of Chronic Hbv In Special Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, studies using sensitive markers of glomerular and tubular kidney function and of bone mineral density have also reported chronic tubular damage and decline of eGFR and bone mineral density in TDF treated patients. 70,[79][80][81][82][83][84][85][86][87] Therefore, it seems appropriate for now to monitor all CHB patients treated with TDF therapy for adverse renal effects with serum creatinine (eGFR) and serum phosphate levels. Moreover, CHB patients at high renal risk undergoing any NA therapy should be monitored with serum creatinine (eGFR) levels.…”
Section: Monitoring Of Patients Treated With Etv Tdf or Taf Recommenmentioning
confidence: 99%
“…In another randomized trial among HBeAg‐positive patients with HBV‐DNA > 7 log IU/mL and normal alanine aminotransferase, 69.4% of patients on TDF combined with emtricitabine versus 45.3% patients on TDF monotherapy could achieve HBV‐DNA < 29 IU/mL . However, in patients with drug resistance, most evidence suggests that combination therapy, either combining TDF with entecavir or combining TDF with emtricitabine, will not increase the chance of complete viral suppression …”
Section: Prevention Of Hepatocellular Carcinomamentioning
confidence: 99%